Penerapan Metode Pertanyaan Tingkat Tinggi untuk Meningkatkan Komunikasi Matematis dan Kreatifitas Berpikir Mahasiswa - Prihatin Ningsih Sagala (Universitas Islam Negeri (UIN) Mataram, 2012)
The profile data of the educational process at the Department of Mathematics UNIMED indicates that the student repeat and failure is still high, especially in the advanced course. In Descrete Mathematics I student I know graduation percentage in 2005 s / d 2007 that the obtained value of A is still low at 17%, the value of B is 39%, 7% gained grade C and 37% to obtain the value of E. One indication that causes this problem is a lack of communication skills and creative thinking mathematically finish its students for a problem that is already supported by some of the concepts that have been previously known. If the issue is offered at the level theorem proving, students should begin where complete confusion. Moreover, at the level of analyzing problems, synthesizing questions, solve problems, and evaluate the matter. The main objective of this research is to improve the skills of teachers in applying the model on a subject, in particular whether the application of the method of high-level questions in subjects Descrete Mathematics I can improve mathematical communication and creative thinking students, this study included classroom action research. Based on action research results obtained, for the participation of students found that students who perform activities such as participation in rubric is the score 1-5 contained 86%. Spike 77.7% overall. To obtain 86% graduation rate or 31 people from 36 students. And from the interviews found that 94% of the students or 34 people out of 36 people found the applied learning method was appropriate and suitable researchers in an effort to improve the communication of mathematical thinking and creativity of students.